The impact of cineole treatment timing on common cold duration and symptoms: Non-randomized exploratory clinical trial. - Andreas Michalsen; Kim Goldenstein; Peter Kardos; Ludger Klimek; Jürgen Palm; Dajana Parganlija; Johannes Stöckl (PLoS ONE, 2024)
Introduction Common cold (CC) symptoms arise from an inflammatory response treatable with cineole and generally peak within two days, which complicates research implementation. We therefore explored the benefits of early cineole administration with enrolment of participants prior to CC onset. Methods Out of 522 adults enrolled in our phase IV, open-label, non-randomized, exploratory clinical trial (EudraCT No. 2020-000860-51), 329 developed a CC and used 200 mg cineole (Soledum®, CNL-1976) t.i.d. for max. 15 (± 2) days. Primary endpoint was burden of disease based on the Wisconsin Upper Respiratory Symptom Survey (WURSS-11). Results Comparing three strata based on time to treatment (≤ 12 h, > 12 to ≤ 24 h and > 24 h), earliest treatment resulted in lowest AUC-WURSS (Spearman correlation coefficient of 0.36) and reduced the overall burden of disease by 38% (p < 0.0001). Earlier and lower symptom severity peak resulted, with shorter time to remission (average 8.9 vs. 10.7 days with latest treatment initiation, p < 0.05), and higher and faster recovering quality of life (p < 0.05). Tolerability was mostly rated as "very good", with adverse events of suspected causal relationship reported in 4.3% of participants. Conclusions Early intervention shows clinical benefits relevant for the effective treatment of CC with cineole.